Estudo da influência das células T reguladoras autólogas e alogênicas numa Reação Mista de Linfócitos (MLR) - Michele Faria Ramos (2018)
Organ transplantation is a clinical strategy to treat patients with functional organ failure, but the major obstacle to the success of clinical transplantation is the rejection of cells. The unsuccessful results of activation alloimmune responses mediated by the T cells, through recognition of alloantigens presented by donor or recipient antigen presenting cells (APCs). Acute rejection can be prevented by prophylactic strategies using immunosuppressive therapy, but these immunosuppressants are unable to prevent chronic rejection. A treatment for chronic rejection has been retransplantation, but organ shortage has also driven research for new therapies to promote operational tolerance in recipients. T regulator cells (Tregs) are potent immune suppressors of immune responses by suppressor cytokines production, direct suppression of effector cells and modulation of maturation and function of antigen presenting cells. Treg cells are involved in the induction and maintenance of tolerance and have been an important study target for therapy associated with induction of operational tolerance. A cellular therapy using CD4+ CD25hi CD127low FoxP3+ regulatory T cells as a strategy of operational tolerance induction has been the subject of studies in various transplants model. A detailed approach to the role of regulatory T cells in this context, achieved a broad understanding of the molecular mechanisms in promoting operational tolerance and enabling therapeutic success. In this paper, we studied the immunoregulatory behavior of Treg cells in an in vitro assay called Mixed Lymphocyte Reaction (MLR) where T lymphocytes of an individual responders when cultured together with the APCs that stimulate another individual to induce allogeneic reactivity in the presence or absence of homotypic or allopidic Treg cells to the APCs for 7 days. Treg cells, CD4+ T cells and APCs were separated by sorting and then plated. CD4+ T cells were marked with CFSE and the proliferation degree was analyzed according to CFSE dilution. The results obtained in this study showed that regulatory T cells are capable of immunosuppressing the proliferation of CD4+ T cells and that allogeneic FoxP3+ CD4+ T cells are good suppression of proliferation inducing in MLR. It was also observed that Treg cells suppressed IFN-γ and TNF-α production in MLR, but did not induce IL-10 secretion. These findings show that Tregs cells are prominent suppression inducers of the activation of CD4+ T cells by APCs, being promising for the development of a cellular therapy.